Development of Energy Efficiency Activities at El Bosque University to Contribute to Climate Change - Jaime Alberto Romero Infante; Andrés Felipe Delgado; Maria Camila Ortiz; Juan Sebastián Leal; Juliana Bernal; Juan Esteban Prada (Universitas Diponegoro, 2023)
This article demonstrate that the increase reached by the University El Bosque promoted by the UIgreenmetric focuses on the Energy and Climate Change approach is important for the organization. The results on calculating the carbon footprint are important for thecommunity of the Forest for having Environmental responsibility, Awareness of the university community, cost savings and Institutional image. By doing that The educational institution installed 1,227 panels solar which contribute to reduce 79.2 tons of CO2 per year, whose function generates a percentage change of 20.11% in the facilities located in Usaquen. The bicycle parking system increased the use of the bicycle as transportation within the community university in more than 100%. Well, before the installation of the new bicycle parking spaces, the bicycle rotation at the University estimated a t 200 bicycles a day, while currently, the average daily turnover of bicycles is estimated at 528. In the first room, the elevators have a system of LED lights, which make the energy consumption related to Cabin lighting is greatly dimmed. They also provide greater durability luminaires and great savings on the bill electrical.